Genome-wide analysis of the polyphenol oxidase gene family reveals that MaPPO1 and MaPPO6 are the main contributors to fruit browning in Musa acuminate - Qin, Fei; Hu, Chunhua; Dou, Tongxin; Sheng, Ou; Yang, Qiaosong; Deng, Guiming; He, Weidi; Gao, Huijun; Li, Chunyu; Dong, Tao; Yi, Ganjun; Bi, Fangcheng (Frontiers in Plant Science, 2023)
Introduction Polyphenol oxidases (PPOs), which are widely present in plants, play an important role in the growth, development, and stress responses. They can catalyze the oxidization of polyphenols and result in the browning of damaged or cut fruit, which seriously affects fruit quality and compromises the sale of fruit. In banana (Musa acuminata, AAA group), 10 PPO genes were determined based on the availability of a high-quality genome sequence, but the role of PPO genes in fruit browning remains unclear. Methods In this study, we analyzed the physicochemical properties, gene structure, conserved structural domains, and evolutionary relationship of the PPO gene family of banana. The expression patterns were analyzed based on omics data and verified by qRT-PCR analysis. Transient expression assay in tobacco leaves was used to identify the subcellular localization of selected MaPPOs, and we analyzed the polyphenol oxidase activity using recombinant MaPPOs and transient expression assay. Results and discussion We found that more than two-thirds of the MaPPO genes had one intron, and all contained three conserved structural domains of PPO, except MaPPO4. Phylogenetic tree analysis revealed that MaPPO genes were categorized into five groups. MaPPOs did not cluster with Rosaceae and Solanaceae, indicating distant affinities, and MaPPO6/7/8/9/10 clustered into an individual group. Transcriptome, proteome, and expression analyses showed that MaPPO1 exhibits preferential expression in fruit tissue and is highly expressed at respiratory climacteric during fruit ripening. Other examined MaPPO genes were detectable in at least five different tissues. In mature green fruit tissue, MaPPO1 and MaPPO6 were the most abundant. Furthermore, MaPPO1 and MaPPO7 localized in chloroplasts, and MaPPO6 was a chloroplast- and Endoplasmic Reticulum (ER)-localized protein, whereas MaPPO10 only localized in the ER. In addition, the enzyme activity in vivo and in vitro of the selected MaPPO protein showed that MaPPO1 had the highest PPO activity, followed by MaPPO6. These results imply that MaPPO1 and MaPPO6 are the main contributors to banana fruit browning and lay the foundation for the development of banana varieties with low fruit browning.